1992
DOI: 10.1182/blood.v79.5.1178.1178
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of proteolytic activity in human bone marrow stromal cells by basic fibroblast growth factor, interleukin-1, and transforming growth factor beta

Abstract: Plasminogen activators (PAs) and/or plasmin may be involved in hematopoietic regulation. These enzymes release biologically relevant cytokines such as basic fibroblast growth factor (bFGF) from matrix and cell surfaces. In addition, transforming growth factor beta (TGF beta) and interleukin-1 beta (IL-1 beta) are converted from inactive to active forms by plasmin. Therefore, we studied the regulation of PAs and their specific inhibitors, PA inhibitor 1 (PAI-1) and PA inhibitor 2 (PAI-2), in human bone marrow s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…In femptomolar concentrations (10)(11)(12)(13)(14)(15) it is chemotactic for fibroblasts (23). At higher concentrations, TGF-␤1 stimulates fibroblasts to increase collagen production (9), while decreasing collagen degradation by suppressing MMP-1 secretion, and increasing TIMP-1 (25) and plasminogen activator inhibitors (PAIs) activity (33,34). The net result of these multiple actions is the accumulation of collagen within the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In femptomolar concentrations (10)(11)(12)(13)(14)(15) it is chemotactic for fibroblasts (23). At higher concentrations, TGF-␤1 stimulates fibroblasts to increase collagen production (9), while decreasing collagen degradation by suppressing MMP-1 secretion, and increasing TIMP-1 (25) and plasminogen activator inhibitors (PAIs) activity (33,34). The net result of these multiple actions is the accumulation of collagen within the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results suggest that the expression of uPAR is dependent on the stage of myeloma cell maturation, with immature cells having the highest expression. uPA can be produced by a number of cell types in the BM environment, making it possible for myeloma cells to bind either endogenously or exogenously derived uPA (Hoekman et al, 1991;Hannocks et al, 1992). The consecutive activation of plasminogen to plasmin will focus proteolytic activity on the surface of the myeloma cells.…”
Section: Discussionmentioning
confidence: 99%
“…TGF␤ 1 has been shown to play a crucial role in the formation and maintenance of the extracellular matrix through mechanisms including modulation of the plasminogen activator system. This has been demonstrated in vitro not only for cultured human epithelial cell lines (Keski-Oja et al, 1988;Arnoletti et al, 1995), but also for cultured human fibroblasts (Lund et al, 1987;Keski-Oja et al, 1988;Hamilton et al, 1991;Hannocks et al, 1992;Cullen et al, 1997).…”
mentioning
confidence: 86%
“…PAI-1 not only inhibits the enzymatic activity of uPA, it can also influence cell migration and prevent cell adhesion (reviewed by Andreasen et al, 1997). In contrast, it has been reported that in human lung-cancer cells (Keski-Oja et al, 1988), and breast-cancer cells (Arnoletti et al, 1995), as well as in human synovial fibroblasts (Hamilton et al, 1991), and bone-marrow fibroblasts (Hannocks et al, 1992), TGF␤ 1 actually increased uPA expression. These differing influences of TGF␤ 1 on PA expression by human cancer cells and fibroblasts of different tissue origin, together with our observations in one of the tumor-derived fibroblast strains (T3), indicate that TGF␤ 1 is not a down-regulator of plasminogenactivator activity in general, and that caution is warranted.…”
Section: Influence Of Factors Released By Human Epithelial-tumor Cellmentioning
confidence: 99%